A magnetorheological clutch for efficient automotive auxiliary device actuation - F. Bucchi; P. Forte; F. Frendo; R. Squarcini (Fracture and Structural Integrity)
In this paper the results of a project funded by Regione Toscana aimed at reducing the power absorption of auxiliary devices in vehicles are presented. In particular the design, testing and application of a magnetorheological clutch (MR) is proposed, aimed at disengaging the vacuum pump, which draws in air from the power-brake booster chamber, in order to reduce the device power absorption. Several clutch preliminary studies done to choose the clutch geometry and the magnetic field supply are illustrated. The final choice consisted in an MR clutch with permanent magnet, which satisfied size, torque and fail-safe specifications. The clutch characteristics, in terms of torque versus slip, were obtained experimentally for three different clutch prototypes on an ad-hoc developed test bench.As result of a preliminary simulation, a comparison between the power absorption of a current production vacuum pump, an innovative vacuum pump and both vacuum pumps coupled with the MR clutch is presented. The New European Driving Cycle is considered for simulating the vacuum pump operation both in urban and highway driving. Results show that the use of the innovative vacuum pump reduces the device consumption of about 35%, whereas the use of MR clutch coupled with the innovative vacuum pump reduces it up to about 44% in urban driving and 50% in highway driving.